2010
DOI: 10.1185/03007995.2010.525028
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomised, crossover study of two doses of a single-tablet combination of ibuprofen/paracetamol and placebo for primary dysmenorrhoea

Abstract: One or two tablets of a single-tablet combination of ibuprofen 200 mg/paracetamol 500 mg is well-tolerated and provides superior analgesic efficacy to placebo in patients with primary dysmenorrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Current understanding of the pathogenesis in primary dysmenorrhea implicates excessive imbalanced amounts of prostanoids and possibly eicosanoids released from the endometrium [21,22]. The majority of subjects benefit from administration of nonsteroidal anti-inflammatory drugs (NSAIDs) [13,23]. A strong negative correlation between dairy product intake and dysmenorrhea and its associated symptoms among university female students was demonstrated whereby the severity of primary dysmenorrhea decreased with increasing daily intake of dairy products [24].…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding of the pathogenesis in primary dysmenorrhea implicates excessive imbalanced amounts of prostanoids and possibly eicosanoids released from the endometrium [21,22]. The majority of subjects benefit from administration of nonsteroidal anti-inflammatory drugs (NSAIDs) [13,23]. A strong negative correlation between dairy product intake and dysmenorrhea and its associated symptoms among university female students was demonstrated whereby the severity of primary dysmenorrhea decreased with increasing daily intake of dairy products [24].…”
Section: Introductionmentioning
confidence: 99%
“…They found that naproxen was significantly more effective than placebo in producing moderate to excellent relief of pain (OR 3.67, 95%CI, 2.94 to 4.58). Fixed dose combinations of paracetamol with NSAIDs also resulted in significant pain relief in women with primary dysmenorrhea [22]. A systematic literature review suggests that a combination of paracetamol and an NSAID may offer superior analgesia for acute pain than either drug alone [23].…”
Section: Discussionmentioning
confidence: 99%
“…Dawood and Khan-Dawood [39] proved that paracetamol and ibuprofen were effective in reducing pain associated with PD; however, ibuprofen was more effective with lower pain scores. Another RCT found that a combination of paracetamol and ibuprofen was more effective than each drug used alone for pain relief in patients with PD [40].…”
Section: Discussionmentioning
confidence: 99%